2020
DOI: 10.1093/labmed/lmaa067
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia Is Associated with COVID-19 Severity and Outcome: An Updated Meta-Analysis of 5637 Patients with Multiple Outcomes

Abstract: The COVID-19 pandemic is persistent worldwide. A prior meta-analysis suggested the association of thrombocytopenia (TCP) with more severe COVID-19 illness and high mortality. Considering newly published studies, we updated the previous meta-analysis to confirm and explain the association of TCP with COVID-19 severity and multiple outcomes. Twenty-four studies with 5637 patients with COVID-19 were included in this study. The weighted incidence of TCP in COVID-19 was 12.4% (95% confidence interval [CI], 7.9%–17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 37 publications
4
45
1
3
Order By: Relevance
“…Platelet count was significantly lower in non-survivors, where about half of them had thrombocytopenia. Compared with the non-survivors, it was found that only one-third of survivors had low platelets (p-value = 0.001); this supports the idea that low platelet count was associated with COVID-19 disease severity, more extended hospital stay, low probability of survival, and subsequent long term mortality [ [36] , [37] , [38] , [39] , [40] ]. Another finding is D-dimer's elevation, especially in non-survivor patients.…”
Section: Discussionmentioning
confidence: 53%
“…Platelet count was significantly lower in non-survivors, where about half of them had thrombocytopenia. Compared with the non-survivors, it was found that only one-third of survivors had low platelets (p-value = 0.001); this supports the idea that low platelet count was associated with COVID-19 disease severity, more extended hospital stay, low probability of survival, and subsequent long term mortality [ [36] , [37] , [38] , [39] , [40] ]. Another finding is D-dimer's elevation, especially in non-survivor patients.…”
Section: Discussionmentioning
confidence: 53%
“…An interesting point of the subgroup analysis is that thrombocytopenia may not be significantly related to intensive care unit (ICU) admission. This aspect could be explained considering that thrombocytopenia tends to reach a significant level in the late clinical stage of COVID-19 ( 8 ).…”
Section: Plateletsmentioning
confidence: 99%
“…Thrombocytopenia, which was more pronounced in MIS-C and correlated significantly with IL15 and IL15/IL15 composite transcript score in both KD and MIS-C, has also been reported in COVID-19 and postulated because of various mechanisms [34][35][36][37][38] . In the case of KD, thrombocytopenia has been found to be associated with disease severity 40 .…”
Section: Integrated Analyses Of Vip/svip Signatures Cytokine Profile and Clinical Laboratory Parameters Reveal Unique Features Of Mis-c Amentioning
confidence: 55%
“…In the case of KD, thrombocytopenia has been found to be associated with disease severity 51 . Similarly, in the case of COVID-19, a large meta-analysis confirmed that approximately 12% of hospitalized patients have thrombocytopenia, which represents a sign of disease severity and poor outcomes 46 .…”
Section: Integrated Analyses Of Vip/svip Signatures Cytokine Profile and Clinical Laboratory Parameters Reveal Unique Features Of Mis-c Amentioning
confidence: 91%